Neurological disorders in COVID-19: a case of Acute Disseminated Encephalomyelitis in an adult patient - Verriello, Lorenzo; Pez, Sara; Pauletto, Giada; D'Agostini, Serena; Nilo, Annacarmen; Gigli, Gian Luigi; Valente, Mariarosaria (Acta Biomedica Atenei Parmensis, 2022)
Abstract Different neurological complications associated with the severe acute respiratory syndrome coronavirus (SARS-CoV-2) infection have been widely documented. Acute disseminated encephalomyelitis (ADEM) is a rare immune-mediated demyelinating disorder, described within the spectrum of neurological manifestations of COVID-19. Herein, we describe a case of adult-ADEM presenting with diplopia and slowly progressive ataxia developed one month after SARS-CoV-2 infection. Brain magnetic resonance imaging (MRI) revealed acute multifocal demyelinating lesions throughout the brain. Other possible etiologies have been ruled out. After treatment with high-dose steroids, we observed a progressive clinical and radiological improvement. A 4-months follow-up showed complete clinical recovery. Although extremely rare, ADEM could be associated to SARS-CoV-2 infection and should be considered in the differential diagnosis. Early recognition of this COVID-19 neurological complication, even in the absence of pulmonary involvement, is important to start a prompt immune-modulatory treatment and, consequently, ensure a good outcome.